Respon Pertumbuhan dan Hasil Tanaman Bayam (Amarantus tricolor L) Terhadap Perlakuan Pupuk Organik Kascing - Sunu Tri Basuki; Bagus Putu Udiyana; I Made Suryana (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
This research is entitled "Response of Growth and Yield of Spinach (Amaranthus tricolor L) Towards the Treatment of Organic Cashing Fertilizer". The study was conducted in the rice fields of Renon Village, East Denpasar, Denpasar City for two months starting from 23 October to 30 November 2019. The purpose of this study was to determine the effect and the best dose of vermicompost organic fertilizer on the growth and yield of spinach plants Parameters observed in the study this is plant height, number of leaves, leaf area, stem diameter, fresh weight of plants above ground, fresh weight of roots, oven dry weight of plants above ground, and oven dry weight of roots. This study used a randomized block design (RBD) consisting of 6 treatments and 4 replications so that 24 treatments were obtained. The results of this study indicate that the best dose of kascing organic fertilizer was obtained at a dose of 9 tons ha-1 (K3) with a fresh weight of plants above the ground of 170.74 g and the oven dry weight of plants above the ground, namely 18.17 g.